1996
DOI: 10.1002/(sici)1097-4652(199603)166:3<568::aid-jcp11>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α: Posttranscriptional stabilization of WAF1 mRNA in p53-deficient human leukemic cells

Abstract: The p53 protein directly regulates the expression of the WAF1 (wild-type p53-activated fragment 1) protein which is a cyclin-dependent kinase inhibitor (CDK1). DNA damaging agents such as ionizing or UV radiation, and some chemical agents induce WAF1 in wild-type p53 containing cells, thereby halting cell cycle progression. WAF1 expression is also induced through a p53-independent pathway. Tumor necrosis factor alpha (TNF alpha) is a cytotoxic/cytostatic compound for some human cancer cells. We examined a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 46 publications
3
37
0
1
Order By: Relevance
“…Thus, even a modest increase in mRNA stability would result in the rapid accumulation of p21waf1/c1~t mRNA. Our findings are consistent with recent reports of an increase in the half-life of p2Iwt1/"p' mRNA in human KG-1 myeloblastic cells after exposure to tumor necrosis factor-a [36], in normal human fibroblasts (Wl38) after exposure to interleukin-I [37] and in HL-60 cells after treatment with TPA or dihydroxyvitamin D, [ 111. Nevertheless, transcriptional activation may contribute to the p53-independent induction of The physiological role of the MAPK-dependent, p53-independent pathway of p2lWaf1/"p1 mRNA induction is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, even a modest increase in mRNA stability would result in the rapid accumulation of p21waf1/c1~t mRNA. Our findings are consistent with recent reports of an increase in the half-life of p2Iwt1/"p' mRNA in human KG-1 myeloblastic cells after exposure to tumor necrosis factor-a [36], in normal human fibroblasts (Wl38) after exposure to interleukin-I [37] and in HL-60 cells after treatment with TPA or dihydroxyvitamin D, [ 111. Nevertheless, transcriptional activation may contribute to the p53-independent induction of The physiological role of the MAPK-dependent, p53-independent pathway of p2lWaf1/"p1 mRNA induction is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…However it should be noted that in some p53 de®cient myeloid leukemic cell lines (K562, HL60), TNF was e cient to induce a cytostatic e ect (Shiohara et al, 1996). This further con®rms that TNF has strikingly di erent e ects according to the cell type.…”
Section: Discussionmentioning
confidence: 91%
“…The reason for including three p53-negative cell lines (HL-60, U937 and K562) (Shiohara et al, 1996) was a reported covalent association between 5.8S rRNA and a C-terminal serine-residue in p53 (Samad and Carroll, 1991;Fontoura et al, 1992). Because (wild-type) p53 expression can induce apoptosis, it was of interest to determine if apoptotic 28S rRNA fragmentation correlated with this p53/rRNA association.…”
Section: Introductionmentioning
confidence: 99%